2020
DOI: 10.1038/s41598-020-73177-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan regulates synapse formation and function in developing neural networks

Abstract: Neurodevelopmental disorders present with synaptic alterations that disrupt the balance between excitatory and inhibitory signaling. For example, hyperexcitability of cortical neurons is associated with both epilepsy and autism spectrum disorders. However, the mechanisms that initially establish the balance between excitatory and inhibitory signaling in brain development are not well understood. Here, we sought to determine how the extracellular matrix directs synapse formation and regulates synaptic function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 78 publications
3
43
1
Order By: Relevance
“…This indicates that CB 1 is closer to the presynaptic marker than the postsynaptic marker and preferentially localizes to the presynapse. The median distance between VGLUT-1 and PSD-95 (0.131 µm) was similar to distance between CB 1 and PSD-95 and is consistent with our previous STORM measurements of synaptic cleft size 26 , 27 . Additionally, we investigated CB 1 localization at inhibitory synapses (n = 47) and observed a significantly shorter ( p = 0.014) median distance between CB 1 /presynaptic marker VGAT (0.046 µm) compared to CB 1 /postsynaptic marker gephyrin (0.062 µm) (Fig.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…This indicates that CB 1 is closer to the presynaptic marker than the postsynaptic marker and preferentially localizes to the presynapse. The median distance between VGLUT-1 and PSD-95 (0.131 µm) was similar to distance between CB 1 and PSD-95 and is consistent with our previous STORM measurements of synaptic cleft size 26 , 27 . Additionally, we investigated CB 1 localization at inhibitory synapses (n = 47) and observed a significantly shorter ( p = 0.014) median distance between CB 1 /presynaptic marker VGAT (0.046 µm) compared to CB 1 /postsynaptic marker gephyrin (0.062 µm) (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Disruptions to the spatial and temporal regulation of synaptogenesis during this critical window is thought to drive developmental disorders such as ASD 20 , 55 . At 90 days of development, we have previously demonstrated that our cortical spheroids exhibit both excitatory and inhibitory synapses 26 , 27 . Furthermore, these synaptic connections exhibit a high level of plasticity, and are readily altered by acute perturbations to either the intracellular cytoskeleton or extracellular matrix 26 , 27 .…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations